The US National Violent Death Reporting System: domestic and international lessons for violence injury surveillance. (14th December 2006) - Weiss, H B; Gutierrez, M I; Harrison, J; Matzopoulos, R
Abstract : Objectives: This article reviews and comments on the development, strengths and limitations of the US National Violent Death Reporting System (NVDRS) from a variety of domestic and international perspectives. Methods: The authors were provided preliminary copies of the manuscripts in this special edition and examined them to understand and put in context the elements and uses of the NVDRS so far. Their comments are based on their reading and interpretation of these papers plus their own combined experience in injury and public health surveillance from four different countries: the US, Colombia, Australia, and South Africa. Results: The NVDRS is bigger than the sum of its parts because it links existing data from multiple sources. Its adoption of modern relational database technologies offers advantages over traditional injury surveillance databases and creates new opportunities for understanding, collaboration, and partnerships. Challenges include overcoming resource limitations so that it can become a truly national system, measuring and improving its sensitivity and comparability, and the need to examine mortality in context with serious non-fatal violent events. Conclusions: The NVDRS is an important work in progress for the US. Each country should examine its own needs, traditions, resources, and existing infrastructure when deciding what kind of violence surveillance system to develop. However, collaboration in developing common definitions and classifications provides an important foundation for international comparisons.